2022
DOI: 10.3389/fmicb.2022.871177
|View full text |Cite
|
Sign up to set email alerts
|

Algicidal Bacteria: A Review of Current Knowledge and Applications to Control Harmful Algal Blooms

Abstract: Interactions between bacteria and phytoplankton in aqueous ecosystems are both complex and dynamic, with associations that range from mutualism to parasitism. This review focuses on algicidal interactions, in which bacteria are capable of controlling algal growth through physical association or the production of algicidal compounds. While there is some evidence for bacterial control of algal growth in the field, our understanding of these interactions is largely based on laboratory culture experiments. Here, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 247 publications
2
45
1
Order By: Relevance
“…Our findings showed that the algicidal compounds of LD-B6 had freeze-thaw stability, were heat tolerant, and were stable under alkaline conditions, while acidic conditions had a significant effect on the algicidal activity ( Figure 6 ). As described in reviews, algicidal bacteria can produce several kinds of algicidal substances, including ectoenzymes (e.g., serine protease and extracellular agarase), pigments (e.g., isatin and prodigiosin) ( Meyer et al, 2017 ; Wang et al, 2020 ; Coyne et al, 2022 ). Based on the thermal stability of algicidal compounds secreted by strain LD-B6, it is unlikely that this compound is a protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings showed that the algicidal compounds of LD-B6 had freeze-thaw stability, were heat tolerant, and were stable under alkaline conditions, while acidic conditions had a significant effect on the algicidal activity ( Figure 6 ). As described in reviews, algicidal bacteria can produce several kinds of algicidal substances, including ectoenzymes (e.g., serine protease and extracellular agarase), pigments (e.g., isatin and prodigiosin) ( Meyer et al, 2017 ; Wang et al, 2020 ; Coyne et al, 2022 ). Based on the thermal stability of algicidal compounds secreted by strain LD-B6, it is unlikely that this compound is a protein.…”
Section: Discussionmentioning
confidence: 99%
“…However, the implementation of chemical and physical methods for the management of HABs is still limited due to the disadvantages of high cost, poor specificity, and secondary pollution ( Yu et al, 2017 ). Biological methods such as the use of algicidal bacteria have been widely studied in the control of HABs because of their advantages of safety and efficiency ( Wang et al, 2020 ; Coyne et al, 2022 ). Studies have shown that about 50% of the algicidal bacteria belong to the Cytophaga/Flavobacterium/Bacteroidetes (CFB) group, and about 45% belong to Gammaproteobacteria.…”
Section: Introductionmentioning
confidence: 99%
“…In aqueous ecosystems, bacteria are capable of controlling massive growth of algae and cyanobacteria through physical association or the production of algicidal compounds (Coyne et al 2022 ). The aquatic bacterium Streptomyces neyagawaensis has been shown to be capable of suppressing the growth of cyanobacteria (such as Microcystis aeruginosa ) and of a wide range of algae, including Chlorella spp.…”
Section: Microbial Antagonistsmentioning
confidence: 99%
“…The bacterium Phaeobacter inhibens can promote growth of the marine alga Emiliania huxleyi at an early stage (mutualistic interaction) but then kill it at a later stage (antagonistic interaction). Bacteria isolated from diatoms of the genus Pseudo-nitzschia display algicidal activity, and a few bacteria exhibit lytic activity against both cyanobacteria and microcystins (Coyne et al 2022 ).…”
Section: Microbial Antagonistsmentioning
confidence: 99%
“…H 2 O 2 (17)(18)(19). On the other hand, they may compete for limited inorganic nutrients (20) and produce algicidal compounds (for a recent review see (21)).…”
Section: Introductionmentioning
confidence: 99%